Factors Affecting Potentially Inappropriate Medications (PIMs) Based on STOPP/START Criteria in Geriatric Patients at RSUD Dr. Soedomo Trenggalek: Faktor-Faktor yang Mempengaruhi Potentially Inappropriate Medications (PIMs) Berdasarkan Kriteria STOPP/START pada Pasien Geriatri di RSUD Dr. Soedomo Trenggalek - Widyaningrum, Esti Ambar; Fitriani, Marina; Irawati, Reny Nur Satya; Fajriyah, Shofiatul; Kurniawati, Evi; Lestari, Tri Puji (Universitas Tadulako, 2024)
Background: Geriatric patients often have multiple comorbidities and decreased physiological function, leading to polypharmacy and potential exposure to inappropriate medications (PIMs). Objectives: This study investigates geriatric inpatients' characteristic profiles, evaluates PIMs using STOPP/START criteria, and explores factors influencing PIM incidence. Method: This study employed a retrospective observational analytical approach. The sampling technique was purposive sampling. The sample involved in this study was 312 patients. Results: The geriatric patients involved in this study had the following characteristics: 62% male and 38% female; 69% youngest-old (65-74 years), 30% middle-old (75-90 years), and 1% oldest-old (>90 years); 87% with BPJS service type and 13% with general service type; main diagnosis groups of the patients were gastrointestinal of 9%, cardiovascular of 31%, respiratory of 3%, neurological of 1%, infection of 11%, endocrine of 13%, genitourinary of 15%, immune an malignant of 1%, blood of 11%, musculoskeletal of 2%, eyes of 2% and skin of 1%; 13% patients had one disease, 43% had two diseases, 25% had three diseases, and 19% had â‰¥ four diseases;29% had 15 drugs, 50% had 6-10 drugs, 17% had 11-15 drugs, 3% had 20 drugs, and 1% had â‰¥ 20 drugs. There were 72 PIMs based on STOPP/START criteria. The results of the analysis using the C contingency coefficient test showed the following factors, such as gender (p-value of 0.894), age (p-value of 0.470), type of service (p-value of 0.166), main diagnosis (p-value of 0.042), number of illness (p-value of 0.106), and number of drugs (p-value of 0.182). Conclusion: There is a correlation between the main diagnosis factor and PIMs with a p-value of 0.042 (p-value < 0.05).